Pilihan Masyarakat pada Agen Biro Jodoh Online: Kebutuhan atau Tuntutan? - Mughni Labib Ilhamuddin Is Ashidiqie (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2020)
The rapid development of technology turned out not only to impact the industrial sector but also to impact the soul mate-searching phenomenon, which is dragged in the flow of its development. One of them is manifested in the form of an online dating agency. However, an interesting discussion is whether the existence of such an online dating agency is a need or demand for those wanting to find a partner. In reviewing the discussion, the author applied a qualitative approach and purposive sampling technique to extract the required data. The research results revealed that most informants did not have their preferences for an online dating agency is searching for a partner. Only one informant stated wanting to use the service, provided the informant has not found a partner within the set deadline. Thus, the online dating agency can be said to be a need when someone is in an urgent situation and condition. Besides, those informants' decisions, both those who had preferences for online dating agencies and those who did not, were rational choices. The reason is that those informants had their preferences in finding a partner. Thus, based on their statements, it can be said that the online dating agency has not become a need as a way to find a partner.